Efeito da história experimental na sensibilidade às contingências em participantes flexíveis e inflexíveis - Zerbinatti, Ana Lídia Fonseca (Universidade Federal de São Carlos, 2016)
This study aimed to investigate whether a previous history of learning by instructional control, in both the previous story of the subject or immediately following an experimental condition, could differentially affect the sensitivity to contingencies. Replicating previous studies, the authors sought to address a possible history of control by following rules, assessing the presence of flexibility or inflexibility indicator’s in their repertoire. Therefore, we evaluated 212 undergraduate students who responded to the Rigidity Scale of Rehfisch; 114 were implemented by virtual media and 98 during individual meeting. Of the 23 participants assessed who met inclusion’s criteria, 13 agreed to participate in the study, seven were recruited by personal application and six through online assessment. Eight participants were males and five females, aged 18-31; nine participants presented scores agreed as flexible and 4 others as inflexible. The experimental condition is the execution of tasks on a matching-to-sample schedule (MTS), arranged in two phases, through appropriate software. In Phase 1, the participants were divided into the training of two different instructional conditions: 1) instructions corresponding to the contingencies programmed; and 2) discrepant instructions. Considering the participants of the Group Flexible, 5 were exposed to instructional correspondence training and 4 the discrepancy; two inflexible participants were assigned to each instructional training conditions. Eleven of thirteen participants reach the learning criteria, required in Phase 1, during 69 or less trials; the two participants who did not meet the criteria were allocated in the Flexible Group (P167 and P184) and were submitted to the discrepant training. In Phase 2 was scheduled during a single experimental condition, similar to all participants, with the presentation of 80 trials, divided into 4 blocks of 20 each. The first and third blocks have been programmed accordingly to the instructions; the second and fourth block presented contingencies that were instructions’ discrepant. Six of the nine flexible participants presented a percentage of responses equal to or greater than 70% accuracy, in the first block of discrepant trials, during the Phase 2; two of the three participants presented lower percentage of correct answers, had a history of learning by discrepant instructions. Participants of the inflexible Group showed higher percentage of correct answers, when they had been subjected to a discrepancy during in training. It was addressed how these results either replicate or present differences from the literature in the area.
Keywords: Comportamento governado por regras; Sensibilidade às contingências; Inflexibilidade; Escala de Rigidez; Estudantes universitários; Rule-governed behavior; Contingency sensitivity; Rigidity Scale; Undergraduate students; CIENCIAS HUMANAS::PSICOLOGIA